Resumption of Positive-Pressure Ventilation Devices for Obstructive Sleep Apnea following Transsphenoidal Surgery: An Institutional Experience of a Surgical Cohort - Gravbrot, Nicholas; Jahnke, Heidi; White, William L.; Little, Andrew S. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives Transsphenoidal surgery creates a skull base defect that may cause postoperative cerebrospinal fluid (CSF) leakage or pneumocephalus. This study reviewed the institutional experience of a pituitary center in managing patients who use positive-pressure ventilation (PPV) devices for obstructive sleep apnea (OSA) after transsphenoidal surgery, which risks disturbing the skull base repair.Design Retrospective review.Setting Pituitary referral center in a major metropolitan medical center.Methods PPV was resumed at the discretion of the treatment team based on intraoperative findings and OSA severity. Perioperative complications related to resuming and withholding PPV were recorded.Participants Transsphenoidal surgery patients with OSA using PPV devices.Main Outcome Measures Intracranial complications before and after resuming PPV.Results A total of 42 patients met the study criteria. Intraoperative CSF leakage was encountered and repaired in 20 (48%) patients. Overall, 38 patients resumed PPV (median: 3.5 weeks postsurgery; range: 0.14–52 weeks) and 4 patients did not resume PPV. Postoperatively, no patient experienced CSF leakage or pneumocephalus before or after resuming PPV. Four (10%) patients required temporary nocturnal supplemental oxygen at home, one patient was reintubated after a myocardial infarction, and one patient had a prolonged hospital stay due to chronic obstructive pulmonary disease exacerbation.Conclusions Resuming PPV use after transsphenoidal surgery did not result in intracranial complications. However, delay in resuming PPV resulted in four patients requiring oxygen at home. We propose a preliminary PPV device management algorithm based on the size of the intraoperative CSF leak to facilitate future studies.
Keywords: CPAP; obstructive sleep apnea; positive-pressure ventilation; transsphenoidal surgery